Evaluasi Penegakan Hukum Tindak Pidana Pencucian Uang: Telaah Atas Putusan Nomor 351/PID.SUS/2022/PN JKT.PST - Pesman Laia; Hudi Yusuf (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Law enforcement against money laundering crimes (MLC) has an essential function in preserving the reliability of financial operations system and the national economy. In the era of globalization and technological advancement, the modus operandi of money laundering has become increasingly complex, requiring serious attention from law enforcement agencies. This crime not only has the potential to destabilize financial systems but can also be used to fund other unlawful acts, including bribery, narcotics trade, and acts of terrorism. Therefore, strengthening the legal mechanisms to prevent and combat money laundering has become an urgent priority. The case processed by the Central Jakarta Court, with Decision Number 351/Pid.Sus/2022/PN Jkt.Pst, involving the defendant Jefry Djoharam, SE, provides a real example in the law enforcement process against money laundering in Indonesia. In this case, the The accused received a prison sentence of 2 years and 6 months. and fined IDR 500 million, along with the seizure of evidence in the form of suspicious financial transaction documents. This verdict reflects the court's efforts to impose a deterrent effect on the perpetrator while upholding justice. However, the impact of this ruling on deterring similar offenses in the future still needs further evaluation. This study aims to evaluate the legal process in handling money laundering crimes involving Jefry Djoharam, SE, and to evaluate the judges legal reasoning as well as the efficacy of the verdict. Additionally, this study also identifies the strengths and weaknesses in the law enforcement system related to money laundering crimes in Indonesia. In this regard, understanding how the implementation of existing regulations works and to assess whether its implementation in the field aligns with the principles of justice and effectiveness. Through document analysis and case study methods, this research investigates the trial proceedings, judicial reasoning, and the verdict’s influence on preventing money laundering offenses. The findings of this study are anticipated to aid in enhancing regulations and law enforcement efforts concerning money laundering and provide constructive recommendations for policymakers and legal practitioners in Indonesia.